STUDY OF THE APPLICATION GREEN CONSTRUCTION IN TESTING THE FUNCTIONAL FEASIBILITY OF MAIN PRAJA OFFICE THE REGIONAL SECRETARIAT OF DENPASAR CITY - I Gusti Agung Gede Jaya Adhiputra; I Nengah Sinarta; Ni Komang Ayu Agustini (Journal of Infrastructure Planning and Engineering, 2024)
The functional feasibility and green construction application in the retrofitting of the Praja Utama office building of the Denpasar City regional secretariat was investigated based on Indonesian regulations PUPR Ministerial Regulation No.21 of 2021 concerning Green Buildings and PP No. 16 of 2021 concerning building functional feasibility testing. Visual observations and structural analysis using SAP2000 software revealed significant damage to structural elements, compromising the building's safety and functionality. A retrofitting plan was developed using Fiber Reinforced Polymer (FRP) to strengthen and repair the damaged components. The green construction assessment showed a high level of compliance, with 12 out of 13 required categories fulfilled in the retrofitting process. The findings highlight the importance of regular structural assessments, timely retrofitting interventions, and the feasibility of incorporating sustainable practices in building rehabilitation projects. The successful application of FRP and green construction principles demonstrates the potential for restoring structural integrity while minimizing environmental impact. Future research could explore the broader application of these methods and develop standardized guidelines for functional feasibility assessments and green construction in retrofitting projects.